Freeskiers' self-organized and unique pathways to world-class performance in big air - Berg-Johnsen, E.; Rudd, J.; Aune, T. K. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Development of expertise in sports is an outcome of a complex process that emerges as dynamic interactions among various sport-specific constraints [1, 2]. The present study investigates the unique pathway to skill acquisition for world-class freeskiers based on the following specific objectives: 1) How world class athletes create the idea for a new big air trick and how they design practice towards mastering the new skill, and 2), How the practice designs align with key skill acquisition principles.